Prediction of a novel prostate-specific antigen density cutoff value and use of transrectal ultrasound-guided prostate biopsy for diagnosis of prostate cancer in Thailand - Rhunsiri, Peera; Sirisopana, Kun; Jenjitranant, Pocharapong (Insight Urology, 2022)
Objective: The measurement of prostate-specific antigen density (PSAD) is a noninvasive and inexpensive practice, which may improve the accurate diagno- sis of prostate cancer. The incidence of prostate cancer in Thailand is relatively low compared with that in Western countries. Therefore, a blanket adoption of the Western cutoff value (PSAD 0.15 ng/ml/cm3) is inapplicable and can lead to unnecessary biopsies. The aim of this study was to determine an optimal PSAD cutoff value for effective diagnosis in Thai men. Materials and Methods: We retrospectively studied transrectal ultrasound-guided prostate biopsies from 542 men with intermediate PSA concentrations ranging from 4 to 10 ng/ml, carried out from January 2011 to January 2017. The area under the receiver operating characteristic curve (AuROC) was used to evaluate the efficacy of PSAD for the diagnosis of prostate cancer. Results: In Thai men who had intermediate PSA concentrations, the AuROC was higher for PSAD in comparison to that of PSA (0.692 vs 0.544). The AuROC using the PSAD cutoff value = 0.20 ng/ml/cm3 was higher than that using the PSAD cutoff value = 0.15 ng/ml/cm3 (0.652 vs 0.626). The sensitivity, specificity, positive predictive value, and negative predictive values were 67.33%, 62.13%, 29.95%, and 89.15%, respectively. Conclusion: PSAD improved the diagnosis of prostate cancer in Thai men with intermediate PSA concentrations. The optimal cutoff value was 0.20 ng/ml/cm3.